(2x + 2) = (3x + -52)
Reorder the terms:
(2 + 2x) = (3x + -52)
Remove parenthesis around (2 + 2x)
2 + 2x = (3x + -52)
Reorder the terms:
2 + 2x = (-52 + 3x)
Remove parenthesis around (-52 + 3x)
2 + 2x = -52 + 3x
Solving
2 + 2x = -52 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
2 + 2x + -3x = -52 + 3x + -3x
Combine like terms: 2x + -3x = -1x
2 + -1x = -52 + 3x + -3x
Combine like terms: 3x + -3x = 0
2 + -1x = -52 + 0
2 + -1x = -52
Add '-2' to each side of the equation.
2 + -2 + -1x = -52 + -2
Combine like terms: 2 + -2 = 0
0 + -1x = -52 + -2
-1x = -52 + -2
Combine like terms: -52 + -2 = -54
-1x = -54
Divide each side by '-1'.
x = 54
Simplifying
x = 54
F(-3) = 4(-3) - 3 = -12 - 3 = -15.
H(2) = -5(2) + 7 = -10 + 7 = -3.
F(-3) + H(2) = -15 + -3 = -18.
The solution is -18.
Answer:
more likely
Step-by-step explanation:
the probability of 0.05 suggests there is a chance of that event happening. A probability of 0 says that such event would never happen. so despite being small the 0.05 chance is higher than the probability of 0